Modern microeconomics - Koutsoyiannis, A. (New York : St. Martin's Press, 1979)
This book provides a thorough exposition of the traditional and the 'modern' micro-theory. I t concentrates on the models of behaviour of the basic economic units, consumers and producers.
Continued by Non-price competition.
Includes index and bibliographic references: p. [553]-569.
uaj 19/09/2014
Loan
Keywords: Microeconomics